Modeling of suspended sediment concentration - case study in Can Gio, Ho Chi Minh city - Le Nguyen, Hoa Tien; Vo Luong, Hong Phuoc (Vietnam Journal of Marine Science and Technology, 2022)
The dynamics of suspended sediments are complicated due to the influence of hydrodynamic factors and the characterization of cohesive sediment properties. A one-dimensional model is built to calculate the vertical distribution of suspended sediment concentration (SSC). In the model, parameters that influence the vertical distribution of SSC include the settling velocity (ws) and the diffusion coefficient (Kz). The settling velocity depends on the cohesive sediment properties, and the diffusion coefficient depends on the wave-current dynamics. The model applies measured data in June 2014 on the mud flats in Can Gio, Ho Chi Minh city, Vietnam. In this study, the settling velocity ws is a constant of 0.64 × 10-6 m/s. The diffusion coefficient depends on water depth, wave action, and tidal currents. Under strong wave - medium current conditions, the average Kz is 2.88 × 10-3 m2/s. Under medium wave - strong current conditions, the average Kz is 6.11 × 10-3 m2/s, while under strong wave - strong current conditions, the average Kz can reach 6.59 × 10-3 m2/s. The resulting simulations demonstrate that the SSC increases rapidly near the bottom layers. Here, the clay sediments are easily disturbed by dynamic conditions. At the bottom layer, the SSC is strongly influenced by the current factor, while the role of the wave factor has not been clearly shown.